2023
DOI: 10.3390/ijms25010124
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Neuroprotection by Ketone Bodies and Ketogenic Diet in Cerebral Ischemia and Neurodegenerative Diseases

Jiwon Jang,
Su Rim Kim,
Jo Eun Lee
et al.

Abstract: Ketone bodies (KBs), such as acetoacetate and β-hydroxybutyrate, serve as crucial alternative energy sources during glucose deficiency. KBs, generated through ketogenesis in the liver, are metabolized into acetyl-CoA in extrahepatic tissues, entering the tricarboxylic acid cycle and electron transport chain for ATP production. Reduced glucose metabolism and mitochondrial dysfunction correlate with increased neuronal death and brain damage during cerebral ischemia and neurodegeneration. Both KBs and the ketogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 230 publications
0
2
0
Order By: Relevance
“…Based on this assumption, research on SOD1 G93A mice indicates that a KetoDi could slow the progression of ALS’s clinical and biological signs ( 17 ). A KetoDi enhances the production of KBs, compounds that neurons can utilize as an energy source in the brain ( 18 ). Since KBs can exert neuroprotective effects, it has been suggested that inducing moderate ketosis through regular consumption of medium-chain fatty acids could be beneficial ( 17 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this assumption, research on SOD1 G93A mice indicates that a KetoDi could slow the progression of ALS’s clinical and biological signs ( 17 ). A KetoDi enhances the production of KBs, compounds that neurons can utilize as an energy source in the brain ( 18 ). Since KBs can exert neuroprotective effects, it has been suggested that inducing moderate ketosis through regular consumption of medium-chain fatty acids could be beneficial ( 17 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, potential KetoDi-related biomarkers may include (but not limited to): (a) elevated levels of BHB and acetoacetate (AA) in blood and cerebrospinal fluid (CSF), which indicate ketosis; (b) improved ATP production, a marker of enhanced mitochondrial function; (c) increased cytochrome c oxidase activity, which indicates better mitochondrial respiratory chain function; (d) reduced levels of isoprostanes, protein carbonyls and/or 8-hydroxy-2′-deoxyguanosine, which reflect oxidation of lipids, proteins and DNA, respectively; (e) elevated superoxide dismutase activity, which indicates improved antioxidant defense; (f) lower levels of C reactive protein and pro-inflammatory cytokines (e.g., TNF-α, IL-1β, and IL-6); (g) elevated BDNG, which associates with neuroprotection and neuronal health ( 18 , 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%